233k views
4 votes
S. Solve the following system of equations algebraically.

3x-y = 0
5x + 2y = 22
Part II: Combine the two equations to eliminate one of the variables. Show the result of this
combination below. (2 points)​

1 Answer

5 votes

Answer:

  • 11x = 22
  • (x, y) = (2, 6)

Explanation:

Twice the first equation can be added to the second to eliminate the variable y.

2(3x -y) +(5x +2y) = 2(0) +(22)

11x = 22 . . . . . . . the result of the combination

__

Solving this gives ...

x = 2

Substituting into the first equation gives ...

3(2) -y = 0

y = 6

The solution is (x, y) = (2, 6).

User Stefan Koell
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.